add maths

posted by .

Function of g is g:x→x-1 over x+2,x not equal to -2.
Find g^2

  • add maths -

    g(x) = (x-1)/(x+2)

    If by g^2 you mean g(g(x)), then

    g(g) = (g-1)/(g+2)
    = ((x-1)/(x+2) - 1) / ((x-1)/(x+2) + 2)
    = -1/(x+1)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. additional maths

    If ƒ: x→x+3 find the function g such that gf : x →x²+4x+5
  2. add maths

    Two functions f and g are defined by f:x→3x+2 and g:x→x^2-2.Obtain expressions for fg and gf.Find the value(s) of x for which f=g?
  3. add maths

    If f:x→4x+5,find the composite function f^2.Hence,find f^2(1over2)and f^2(-2) ?
  4. add maths

    Find f^-1 in similar form for each of the following functions. Question no. 1 ↓ f:x→3x over x-3,x not equal to 3 Question no. 2 ↓ f:x→2x+4 over 2x-1,x not equal to 1over2
  5. add maths

    A function f is defined by f:x→x+10 over x-8,x not equal to 8.Find the values of x for which f^-1(x)=x.
  6. add maths

    A function f is defined by f:x→x+1 over x-1,x is not equal to 1.If f^2(2)=3f^-1(k),find the value of k.
  7. add maths

    Functions f and g are defined by f:x→3 over x+2,x is not equal to k and g:x→2x+1. No.1~State the value of k
  8. add maths

    Functions f and g are defined by f:x→3 /(x+2),x is not equal to k . No.1~State the value of k
  9. add maths

    A function f is defined by f:x→(x+1)/ (x-1), x is not equal to 1. If f^2(2)=3f^-1(k),find the value of k.
  10. add maths

    Function f and g are defined by f:x→4-x and g:x→px^2+q where p and q are constants.Given that the composite function gf:x→x^2-8x+11,find the values of p and q.

More Similar Questions